If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9m + -17 = -17 + m Reorder the terms: -17 + 9m = -17 + m Add '17' to each side of the equation. -17 + 17 + 9m = -17 + 17 + m Combine like terms: -17 + 17 = 0 0 + 9m = -17 + 17 + m 9m = -17 + 17 + m Combine like terms: -17 + 17 = 0 9m = 0 + m 9m = m Solving 9m = m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 9m + -1m = m + -1m Combine like terms: 9m + -1m = 8m 8m = m + -1m Combine like terms: m + -1m = 0 8m = 0 Divide each side by '8'. m = 0 Simplifying m = 0
| 5/x=0.6 | | -3.2x+2.58=-3.5 | | -9(v+5)=6v+15 | | (6d+2)(7d-5)= | | -2a+15+4a=6a-9a | | 8.7y-4.6=59.78 | | 1=.4x-.5x-6 | | 4(x+3)-3x=25+3x | | Y-7.9=-1.27 | | 16n+20=17n+12 | | -8+2y=-16 | | 8-y+6+b=13 | | X+23.1=16.6 | | 270/30 | | 6(2f+fh)= | | -3(1+9x)+8= | | 5r^-2/7r^5 | | 7=0.7+b | | 14x+68+14x-7=16x-5 | | 10+(-22)= | | -2=3+5u | | 12f+48h= | | Y=0x+b | | 2w^2+13w=7 | | 5/(1-sqrt3) | | 6[2-7(6-1)]= | | 3=2y-5 | | x^1/2=(3x-12)^1/2 | | X-9+3= | | 4(ax+3)-3x=25+3x | | [3-8(1-4)]= | | 120=3/4y=60 |